Pemanfaatan Tepung Cangkang dan Kepala Udang Vaname (Litopenaeus vannamei) terhadap Penurunan Hiperkolesterolemia secara In Vivo - Rosdiana Ngitung; Sahribulan; A. Sri Rahmadani (Jurusan Biologi Universitas Negeri Makassar, 2022)
This research is an experimental study that aims to determine the effect and optimum concentration of shelland head of white shrimp (Litopenaeus vannamei) on reducing hypercholesterolemia in mice (Mus musculus).This study consisted of 4 treatment groups: P0 (hypercholesterol feed mixed with 0% shrimp shell and head flour),P1 (hypercholesterol feed mixed with 5% shrimp shell and head flour), P2 (hypercholesterol feed mixed with 7%shell and shrimp head flour), and P3 (hypercholesterol feed mixed with 9% shell and shrimp head flour). Theresearch method consisted of the manufacture of hypercholesterolemic feed, the manufacture of shell and shrimphead flour, the manufacture of test animal feed, treatment of test animals, and measurement of cholesterol levels.Data were analyzed using One Way ANOVA and Duncan's test. The average value of initial cholesterol levels inthe P3 treatment group was very significantly different from the P0, P1, and P2 treatment groups. The mean valueof final cholesterol levels in the P2 treatment group was significantly different from P0 and significantly differentfrom P1 and P3. The optimum concentration was 7% (P2) which was able to reduce hypercholesterolemia in mice(Mus musculus) by 0.29%.